DICHOTOMOUS APPROACH TO POVERTY AS A SOURCE OF MODERN TERRORISM - Zelenkov, Mikhail; Boykova, Galina; Boykov, Sergey; Bikov, Mikhail; Rezakov, Ravil (Revista Inclusiones, 2020)
The main purpose of the work is to analyze the dichotomous approach to assessing the impact of the poverty level in society on the growth of the number of terrorists in the 21st century and, on the basis of the results obtained, to justify the place of poverty in the rating of sources of modern terrorist activity. The theoretical basis of the research is a set of scientific papers that examine the relationship between socio-economic trends and terrorist activities, the results of sociological surveys and statistical data.